Petrophysical and geochemical characterization of sediments filling V‐shaped ditches of Roman camps in Moravia, Czech Republic: Filling processes and the role of pedogenesis. Issue 5 (14th April 2020) - Lenďáková, Zuzana; Bábek, Ondřej; Komoróczy, Balázs; Vlach, Marek; Hüssen, Claus‐Michael; Rajtár, Ján
Abstract: The infilling of defense structures (ditches) of the Roman temporary camps in South Moravia (Czech Republic) were studied quantitatively to characterize the ditch‐filling processes, role of pedogenesis, and the effect of geological setting. Samples of soil and sediment were taken from ditch profiles at three sites in South Moravia, Czech Republic ( Pasohlávky, Přibice, and Charvátská Nová Ves ) and three shallow control cores located in close vicinity to the ditches. Physical and chemical parameters (grain size analysis, magnetic susceptibility, element geochemistry, and sediment color analysis) were measured in combination with lithological descriptions. The primary infilling processes were colluviation and pedogenesis, largely controlled by the nature of the geologic substrate in which the ditches are excavated. The dependence of the magnetic susceptibility to iron ratio on grain size are highlighted as a useful proxy of detecting depositional processes within the ditches. High values of the Fe‐normalized magnetic susceptibility together with the frequency‐dependent magnetic susceptibility indicate a strong magnetic enhancement of the upper parts of the ditch filling, particularly in the top soil. This study demonstrates the potential for specific chemical and physical proxies to characterize the depositional history of Roman ditches when limited to coring.